Irreparable Rotator Cuff Tears: A Biomechanical Comparison of Superior Capsuloligamentous Complex Reconstruction Techniques and an Interpositional Graft Technique. Issue 8 (20th August 2019) - Leschinger, Tim; Besch, Katharina; Aydin, Cansu; Staat, Manfred; Scaal, Martin; Müller, Lars Peter; Wegmann, Kilian
Background: Irreparable rotator cuff tears lead to superior translation of the humeral head. Numerous surgical management options are available to treat the condition. Purpose: To compare superior capsule stability among different types of patch grafting in irreparable rotator cuff tears. Methods: Six cadaveric shoulders were tested in a custom-designed shoulder testing system. Superior translation of the humerus and subacromial contact pressure were quantified in an intact condition (condition 1), after cutting the supraspinatus tendon (condition 2), and after additionally cutting the superior capsuloligamentous complex (condition 3). The results were compared among 3 types of patch grafting, in which capsule reconstruction was achieved by glenoidal 3-point (condition 4) or 2-point (condition 5) fixation or by affixing a graft below the acromion (condition 6). Results: No significant difference in subacromial pressure was measured by reconstruction with 2 or 3 anchors compared with conditions 1 and 2 ( P > .05). However, with 3-point fixation, lower levels of pressure were measured than with 2-point fixation. Moreover, superior translation values were lower with 3-point fixation; the same applied for values of the preserved capsule as compared with the torn capsule. In condition 6, a significant increase in pressure in the neutral position was documented ( P < .05). Conclusion: The superior capsuloligamentous complex plays an important role in stabilizing the glenohumeral joint. The results suggest that with additional medial anchoring at the coracoid base, the depressing and centering effect of the superior complex can probably be regained in a more physiological way compared with a reconstructed capsule with 2 glenoid attachments or with an interpositional graft below the acromion.